2018
DOI: 10.1097/md.0000000000011546
|View full text |Cite
|
Sign up to set email alerts
|

Repair or replacement for severe ischemic mitral regurgitation

Abstract: Background:The best surgical option for severe ischemic mitral regurgitation (IMR) is still controversial. The aim of this study was to perform a meta-analysis to compare the clinical outcomes of mitral valve repair (MVP) with replacement (MVR).Methods:A literature search was conducted in PubMed, Embase, and Medline using the terms “ischemic mitral regurgitation” and “repair or annuloplasty or reconstruction” and “replacement” in the title/abstract field. The primary outcomes of interest were perioperative mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…While mortality did not differ between groups in the CTSN trial, the trial was not powered to detect differences in survival. In contrast, a recent meta-analysis that included this CTSN trial [19] and previous five meta-analyses [20][21][22][23][24] reported lower 30-day mortality associated with MVr compared to MVR.…”
Section: Discussionmentioning
confidence: 56%
“…While mortality did not differ between groups in the CTSN trial, the trial was not powered to detect differences in survival. In contrast, a recent meta-analysis that included this CTSN trial [19] and previous five meta-analyses [20][21][22][23][24] reported lower 30-day mortality associated with MVr compared to MVR.…”
Section: Discussionmentioning
confidence: 56%
“…While mortality did not differ between groups in the CTSN trial, the trial was not powered to detect differences in survival. In contrast, a recent meta‐analysis that included this CTSN trial 19 and the previous five meta‐analyses 20–24 reported lower 30‐day mortality associated with MVr compared to MVR.…”
Section: Discussionmentioning
confidence: 69%
“…Similarly, MVP patients with associated heart failure had more percutaneous mitral procedures. Secondary MR was associated with poor prognosis, and the efficacy of surgical treatment and percutaneous MVR is still being discussed [ 13 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%